Transformasi Tafsir Al-Qur’an Di Era Media Digital: Analisis Metodologi Tafsir Dalam Channel Youtube Kajian Tafsir Al-Ma’rifah - Hartati Yuningsih, Abdul Ghany (Al-Qudwah)
The transformation of Qur'anic exegesis methodology through digital platforms has revolutionized the way the science of tafsir is conveyed and received by the public. The limitations of accessibility and interactivity in traditional methods, which rely on oral and written explanations, have necessitated a new, more engaging, and interactive approach through digital technology. The purpose of this research is to analyze and evaluate the methodology of Qur'anic interpretation used in the tafsir studies on the YouTube channel "Kajian Tafsir Al-Ma'rifah" by Musthafa Umar. This study is descriptive qualitative research utilizing a literature review method. Primary data was collected from the tafsir study videos on the "Kajian Tafsir Al-Ma'rifah" YouTube channel, while secondary data was obtained from textbooks, scholarly articles, and relevant tafsir books. The findings of the research indicate that the use of visual and audio elements in the tafsir videos enhances understanding and information retention among the audience. Additionally, interactive features such as comments, likes, and shares create a dynamic dialogue between the interpreter and the audience, strengthening engagement and participation in the learning process. Digital technology, through platforms like YouTube, not only facilitates access to Qur'anic exegesis but also enriches its delivery methods, making it more inclusive and effective in reaching a global audience. This research contributes to the literature on the transformation of tafsir methodology in the digital era and provides practical recommendations for the development of dakwah through digital platforms.